EFFECT OF STEP PATTERN TECHNIQUE TO SIDE AND MOVEMENT STEP STRAIGHT AHEAD TO SABIT KICKNESS - Julianur Julianur; Januar Abdilah Santoso; Jeane Betty Kurnia Jusuf; Andri Tria Raharja; Nanda Alfian Mahardhika (Acitya: Journal of Teaching and Education, 2020)
This study aims to determine the effect of exercise on stepwise pattern and exercise a straight forward move towards crescent kick agility in UKM PSHT students of Muhammadiyah University of East Kalimantan (UMKT). The population in this study were students who were still actively participating in the UKM PSHT UMKT. Sampling uses a random sampling system, divided into 2 groups, namely group A by practicing stepwise patterns and group B by practicing a straight forward step. Each group consists of 10 sample people, so the total sample is 20 people. The results showed that: (1) There was the effect of training the step-by-step pattern on crescent kick agility on UMKT PSHT UKM students who obtained the value of tcount = 9.531> t table = 2.262 with a probability value of 0.000 <α 0.05. (2) There is the effect of a straight-forward exercise on crescent kick agility on UMKT PSHT UKM students who obtained a tcount = 6.975> t table = 2.262 with a significance probability value of 0.000 <α 0.05. (3) There is a difference in the effect of step-to-side pattern training and straight-forward motion training on crescent kick agility in Mulawarman University PSHT UKM students by obtaining a tcount = 4.348> t table = 1.734 with a significance probability value of 0.000 <α 0.05.